Recent Developments and Perspectives in the C-Se Cross Coupling Reactions - Jose, Diana E.; Kanchana, U. S.; Mathew, Thomas V.; Anilkumar, Gopinathan (Current Organic Chemistry, 2020)
The C-Se bond forming reactions are attractive synthetic strategies for biochemists and synthetic chemists alike for the synthesis of various molecules that are of biological, pharmaceutical and material interest. Therefore, the design and synthesis of organoselenium compounds currently constitute engaging fundamental problems in applied chemistry both in pharmaceutical and academic laboratories. This review discusses the recent works reported in carbon–selenium cross-coupling reactions with the emphasis on the mechanistic aspects of the reactions. The reacting species, the addition of ligands, selection of catalysts, use of suitable solvents, proper setting of reaction time, are well discussed to understand the detailed mechanism. Various simple, economical and environmentally friendly protocols are demonstrated, which ensured product stability, low toxicity, environmentally benign and excellent reactivity for the synthesis of organoselenium compounds. This review covers the scientific literature from 2010 to 2019.
Keywords: pharmaceutical